Does Assertiveness and Friendliness Affect a Person's Satisfaction With Social Support? - Teh, H. P.; Teoh, H. J.; Pillay, S. K.; Kannan, K. (Faculty of Psychology, Universitas Surabaya, 2006)
The purpose of this study was to examine whether assertiveness and friendliness affect young adults' satisfaction with their social support. 93 young adults between the ages of 18 to 35 year-old participated in this study. The subjects were required to complete three sets of questionnaires consisting of